A COMPARATIVE ESTIMATION OF MAINTENANCE OF MOBILE PHOSPHORUS IN DIFFERENT GENETIC HORIZONS OF ORDINARY CHERNOZEM - Крамарьов, С. М.; Крамарьов, О. С.; Христенко, А. О.; Токмакова, Л. М.; Жученко, С. І.; Сироватко, В. А.; Цьова, Ю. А.; Сироватко, К. В. (Scientific Progress & Innovations, 2015)
Ordinary chernozem on the loess breeds of heavy granulometric composition of north Steppe zone of Ukraine contain the promoted amount of patitapaban chemical compounds. As a result of this the use of any acid methods, including GOST 26204-91 (Chirikov’s method) results in the substantial artificial overstating of estimation of the phosphatic state of soils (on 40–80 mgs of Р2О5/kg of soil). For diagnostics of the phosphatic state of these soils (in obedience to the requirements of normative documents of Ukraine) it is necessary to use the followings standards: GOST 4114 (Machigin’s method), GOST 4727 (method of Karpinskiy-Zamyatina) and GOST ISO 11263 (method of Olsen). Natural material well-being of arable layer of chernozem ordinary phosphorus matches the limit of low and middle well-being this element of the plants feed, that is confirmed the known empiric information about high efficiency of phosphoric fertilizers on these soils. The arable layer of soils, which contains the remaining phosphates of fertilizers, and also overhead humus horizon of virgin soils has high level of phosphorus. Therefore, for the receipt of high harvests with high quality on chernozem ordinary of north Steppe of Ukraine it is necessary to bring in not less phosphoric fertilizers, that on other soils of country (based on information of gravel diagnostics).